The Effectiveness Of Using Aluminum Foil Baby Scard To Prevent Hypothermi In Lbw At Abdul Manam Simatupang Hospital - Ririn Anggriani; Selvi Puspan Sari (Institute of Computer Science (IOCS), 2021)
The causes of maternal death have changed, where bleeding and infection tend to decrease while the proportion of preeclampsia-eclampsia is increasing. The general purpose of the study was to find out the relationship between pre-eclampsia and the action of Sectio Caaesaria at Abdul Manan Simatupang Hospital in 2021. This research method uses quantitative methods with a cross sectional approach. The population of this study amounted to 73 with a sample of 73 mothers who gave birth by using a total sampling technique. The research instrument used an observation sheet. The data analysis technique used descriptive analysis and chi square test. The results showed that of the 73 respondents who gave birth, the majority experienced severe eclampsia as many as 41 people and 38 people who received Sectio Caesarea (52.1%). Meanwhile, of the 32 mothers who suffered from mild preeclampsia who received Sectio Caesarea, 8 people (11.0%). The results of the chi-square test are known that the significant value of p value is 0.000 (p <0.05), then Ho is rejected so that in this study there is a significant relationship between pre-eclampsia and sectio caesaria at Abdul Manan Simatupang Hospital in 2021. The conclusion is that there is a relationship between pre-eclampsia and sectio caesarea. Suggestions for this study are expected for health workers to be able to detect complications of pregnancy and childbirth as early as possible in order to minimize the incidence of severe pre-eclampsia